CO2 laser supraglottic resurfacing for non-granulomatous chronic supraglottitis in two children. (May 2019) - Smith, Matthew M.; Nokso-Koivisto, Johanna; Leader, Brittany A.; Wilcox, Lyndy J.; Rutter, Michael J.
Abstract: Chronic epiglottitis and supraglottitis are clinical entities that present with respiratory distress and are primarily associated with autoimmune disorders, gastroesophageal reflux disease, or angioedema. First described in adults with sarcoidosis in 2010, CO2 laser epiglottis resurfacing has been effective in reducing epiglottic edema. We present two cases of adolescent males with non-granulomatous chronic supraglottitis who were successfully treated with CO2 laser supraglottic resurfacing.